1989
DOI: 10.1111/j.1365-2826.1989.tb00138.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect on Vasopressin Release of Microinjection of Cholinergic Agonists into the Paraventricular Nucleus of Conscious Rats

Abstract: We have studied in conscious unrestrained rats under basal conditions the effect of activation of muscarinic and nicotinic receptors in the paraventricular nucleus on vasopressin secretion and mean arterial blood pressure. The microinjection of oxotrernorine (0.2, 2 or 20 ng), a specific muscarinic agonist, produced a substantial, dose-dependent, transient increase in the plasma vasopressin concentration. There was also a rise in mean arterial blood pressure and a bradycardia that followed the same time-course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Agonists acting on muscarinic cholinoceptors have been shown to release vasopressin and oxytocin in the rat and this release is blocked by atropine (Kuhn & McCann, 1971;Kuhn, 1974;Clarke & Merrick, 1978;Bisset & Chowdrey, 1984;litake et al, 1986;Shoji et al, 1989). In our experiments, NSTX acted selectively on nicotinic, and not on muscarinic, receptors.…”
Section: Discussionsupporting
confidence: 52%
“…Agonists acting on muscarinic cholinoceptors have been shown to release vasopressin and oxytocin in the rat and this release is blocked by atropine (Kuhn & McCann, 1971;Kuhn, 1974;Clarke & Merrick, 1978;Bisset & Chowdrey, 1984;litake et al, 1986;Shoji et al, 1989). In our experiments, NSTX acted selectively on nicotinic, and not on muscarinic, receptors.…”
Section: Discussionsupporting
confidence: 52%
“…The response was blocked by EAA antagonists (Gribkoff & Dudek, 1990;Gribkoff, 1991). Recently it has been shown that oxotremorine, an agonist acting selectively on muscarinic cholinoceptors, induces an ADR on microinjection into the SON or PVN (Mori et al, 1984) or release of AVP into the circulation on injection into the PVN but not the SON; nicotine caused release on injection into the SON (Shoji et al, 1989;Ota et al, 1992 CNQX are consistent with differences in the anatomy of the cholinergic and noradrenergic innervation of the SON and PVN. The noradrenergic input is derived mainly from the Al group of neurones in the ventrolateral medulla (Sawchenko & Swanson, 1981).…”
Section: Introductionsupporting
confidence: 61%
“…Although the roles of the peripheral RAS are well established, there is still an ongoing debate related to the contribution and mechanisms by which the central RAS influences cardiovascular control (43,52). For example, all RAS components are expressed in the SON and PVN (29), as well as ANG II and AT 1 Rs, have been proposed as key players underlying RAS-mediated increases in sympathoexcitatory outflow and VP systemic release (24,35,42,53). However, recent studies have provided evidence for the lack of AT 1 Rs and ANG II type 2 receptors on presympathetic and VP cells (9 -11), whereas others have supported the contribution of astroglial cells as alternative cellular targets mediating central ANG II actions in these neuronal populations (3,49).…”
Section: Perspectivesmentioning
confidence: 99%
“…it is now well accepted that all components of the RAS are also present within the central nervous system, which, acting independently of the peripheral RAS, can directly influence autonomic and neuroendocrine outflows to the cardiovascular system (8,16). For example, activation of the brain RAS, involving predominantly ANG II and ANG II type 1 receptors (AT 1 Rs), increases sympathoexcitatory outflow and vasopressin (VP) systemic release (24,35,42,53). Despite this evidence, there is still an ongoing debate regarding the localization, sources, cellular targets, and roles of the main RAS components within the brain.…”
mentioning
confidence: 99%